Fatty Acid Composition of 16 Groundnut (Arachis hypogaea, L.) Cultivars grown under Malaysian Conditions - Berry, Shiv K. (1982)
Groundnuts from 16 Arachis hypogaea L. cultivars were found to contain oil in the range of 43 to 50%. Gas-liquid chromatographic analysis of the oil fatty acid methyl esters revealed the occurrence of palmitic (12.22 to 13.30%), stearic (3.17 to 3.67%), oleic (37.94 to 41.90%) linoleic (34.59 to 37.51%), arachidic (1.63 to 1.85%) eicosaenoic (0.99 to 1.22%), behenic (3.24 to 4.36%), and lignoceric (1.08 to 1.44%) as the major fatty acids. Cultivars Tainang 7, Kidang and Alabama were high in oil content and contained relatively low levels of behenic acid and a high oleic/linoleic acid ratio in their oil.